Quick Computing CFD Model to Predict Chemical Pollution in Room - Biliaiev, M. M.; Biliaieva, V. V.; Berlov, O. V.; Kozachyna, V. A.; Mashykhina, P. B. (Science and Transport Progress, 2024)
Purpose. The problem of accidental contamination of workspaces attracts special attention, since in the event of such extreme situations, intense chemical contamination of the air in work areas occurs. This poses a threat of toxic exposure to workers. When assessing the consequences of such situations, it is necessary to take into account the time factor, in particular, to quickly determine the creation of concentrations of chemically hazardous substances. In this regard, an urgent task is to develop effective mathematical models for rapid assessment of the consequences of extreme situations in the working areas of chemically hazardous facilities. The paper considers a CFD model for analyzing the process of chemical air pollution in a workspace during an accidental release of a chemically hazardous substance. The solution of the problem is based on the numerical integration of the fundamental equations of continuum mechanics. Methodology. To calculate the air velocity field in the working room during the operation of supply and exhaust ventilation, a mathematical model of the motion of an inviscid fluid was used. The equation of convective diffusion motion was used to calculate the concentration of a chemically hazardous substance in the workspace. The integration of the modeling equations was carried out using finite difference schemes. Findings. A dynamic model has been created to calculate the spread of a chemically hazardous substance in a workspace. On the basis of the built CFD model, a computer program was created to conduct a computational experiment. Originality. A CFD model has been created to predict the level of air pollution in a workspace in the event of toxic gas emissions. The model is based on the fundamental equations of aerodynamic mechanics and mass transfer. The model makes it possible to determine the effect of the ventilation mode, the intensity of emission of a chemically hazardous substance, the location of equipment in the workspace, and the dynamics of the formation of concentration fields. Practical value. The developed CFD model can be used to quickly analyze the consequences of accidental emissions of a chemically hazardous substance in a workplace and assess the risk of toxic exposure of workers.